(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Toxoplasmosis is an infectious disease caused by Toxoplasma gondii and transmitted to humans by consumption of raw meat or foods contaminated with feces of infected cats. Infection during pregnancy may be transmitted to the fetus causing significant morbidity and mortality. This study is a cross sectional study conducted on (98) pregnant women attending Babylon Maternity and Pediatrics Teaching Hospital during February 2019 who are aged (17-40) years with a mean age of (25.0 ± 4.9), and aims to evaluate their knowledge about the disease, its role in pregnancy, effects on the fetus, and their practice toward its prevention. Significant knowledge difference was found between urban and rural residents. Similarly, educational level had significant impact on knowledge. In conclusion, the study found that Iraqi pregnant females have medium knowledge about toxoplasmosis, but have poor knowledge about its vaccine. However, their practices are generally good in favor of preventing its transmission.